The Impact of Teams Games Tournament Model Assisted by Scratch Media Understanding of Science Concepts - Maulana, Rizky; Rahayu, Puji; Hikmatunisa, Nenden Permas (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This research investigates the impact of the Teams Games Tournament (TGT) cooperative learning model, supplemented by Scratch media, on elementary students' understanding of Natural Science (IPA) concepts. The study addresses the critical issue of inadequate comprehension of IPA concepts among students, as highlighted in prior research. Utilizing a quasi-experimental design with both pretest and posttest assessments, fourth-grade students from an elementary school in West Jakarta were divided into two groups: an experimental group implementing TGT with Scratch and a control group engaged in traditional collaborative learning. The results indicated a significant improvement in the experimental group, which achieved an average posttest score of 85.00, in contrast to 74.00 in the control group, with a p-value of 0.01. These findings suggest that the TGT model, when integrated with Scratch media, enhances students' understanding of IPA concepts. This study advocates for the broader implementation of this instructional approach to foster better comprehension in science education.